Academic Supervision Practices of School Principals and Teacher Competence Improvement in Primary Schools of Pidie Jaya Regency - Cut Mardiyati Isfa; Munawar Munawar; Siraj Siraj (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study investigates the implementation of academic supervision by school administrators as an approach to enhance teacher competency in primary schools of Pidie Jaya Regency, Indonesia. Although being mandated as a systematic approach to improve instructional quality, the execution of academic supervision in numerous institutions is inconsistent. Data were gathered utilizing a qualitative descriptive methodology through in-depth interviews, non-participant observations, and document analysis at SD Negeri 2 Meureudu and SD Negeri 13 Trienggadeng. The results indicate that academic supervision occurs in three primary phases: planning, implementation, and evaluation. Principals establish supervisory objectives, develop instruments, and create timetables according to instructor requirements. Implementation is monitored via classroom observations, coaching sessions, and professional support. The evaluation phase encompasses feedback provision, reflection, and subsequent programming. The research concludes that systematic and collaborative academic supervision substantially enhances teachers' educational, professional, social, and personal competencies. Enhancing supervisory techniques through enhanced principal competencies, systematic tools, and regular follow-up is crucial for improving instructional quality in elementary schools.